PERAN POSITIONING STRATEGI DALAM MEMEDIASI ORIENTASI PASAR DAN KUALITAS PRODUK DAN PENGARUHNYA TERHADAP KINERJA PEMASARAN - Nur Ainun Alwi; Ahmad Firman; Muhammad Hidayat; Mashur Razak (AkMen JURNAL ILMIAH, 2023)
This research is a quantitative research with sampling techniques using survey methods, namely activities to collect data regarding facts. Data were obtained by distributing questionnaires using a Likert scale. This study aims to determine the effect of market orientation and product quality on marketing performance through a positioning strategy at PT Matahari Department Store, Ratu Indah Mall Makassar branch. The population used in this study were consumers of PT Matahari Department Store branch of Mall Ratu Indah Makassar, totaling 100 people. The number of samples cannot be factor analyzed if the number is less than 50, the sample must be 100 or more. The data analysis method in this study is Partial Least Square using the Smart PLS application The research results show that 1) market orientation has no effect on marketing performance 2) product quality has an effect on marketing performance, 3) positioning strategy has had an effect on marketing performance, 4) orientation has had an effect on positioning strategy, 5) product quality has had an effect on positioning strategy, 6) market orientation affects marketing performance through positioning strategy, 7) product quality affects marketing performance through positioning strategy at PT. Matahari Department Store Ratu Indah Mall Makassar Branch.